Affine Poisson & non-Poisson trace principles for Ḣ−1<−α≤−12(Rn−1≥2). (March 2020) - Lombardi, N.; Xiao, J.
Abstract: This note discovers not only an affine non-sharp-Poisson trace inequality but also its sharp-non-Poisson version for a Sobolev function with the fractional antiderivative.